Uncovering potential: dynamic assessment of non-verbal reasoning ability in educationally disadvantaged children - Gewer, Anthony (My University, 2014)
South African research into dynamic assessment has contributed to the growing body of international research which supports the efficacy of dynamic assessment in uncovering learning capacity in a variety of populations of learners with special needs. This study investigated the application of dynamic assessment to a sample of black children within a South African township clinic setting. Aged 9-15 years (mean age = 10.96) they had been referred to the clinic with learning difficulties. The experimental group (n=48) was exposed to a group dynamic assessment process, using certain tasks of the Learning Propensity Assessment Device (LPAD). Their performance was assessed prior to and following the mediated learning intervention. Using Analysis of Covariance, comparisons of pre and post-test scores combined with an innovative qualitative scoring method designed by Lurie and Kozulin (1996) yielded positive findings for the experimental group as compared with a control (n=24) not exposed to mediation. Results of the Raven's Coloured Progressive Matrices (RCPM) and the Rey-Osterreith Complex Figure Test (ROCFT), suggest that the intervention yielded changes, not only in the scores attained, but also in the quality of the responses on the post-tests.
Keywords: Academic achievement--Testing; Children with social disabilities--Education--South Africa; Learning Potential Assessment Device; Children--Intelligence testing--South Africa